2017
DOI: 10.1111/echo.13743
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical anthracycline‐induced cardiotoxicity in long‐term follow‐up of asymptomatic childhood cancer survivors: Assessment by speckle tracking echocardiography

Abstract: Despite normal EF and FS, children exposed to anthracycline therapy may have late-onset subtle changes of LV strain values measured by STE. Whether these changes of strain can predict future risk of developing heart failure needs to be explored in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 31 publications
(55 reference statements)
5
25
1
2
Order By: Relevance
“…26 Recently published study of Çetin et al also showed lower global longitudinal and radial strain values compared to control in asymptomatic childhood cancer survivors with normal left ventricle ejection fraction and fractional shortening. 27 Majority of these findings of two-dimensional speckle tracking analysis-based strain studies are consistent with the present study's result such as reduced global longitudinal and circumferential strain and strain rate values in survivors of childhood cancer compared to controls and negative impact of total anthracycline dose on the left ventricle function. Based on the recommended imaging surveillance frequencies in the long-term follow-up guidelines published by the Children's Oncology Group, patients were classified as high risk who had ≥ 300 mg/m 2 cumulative anthracycline dose at any age.…”
supporting
confidence: 91%
“…26 Recently published study of Çetin et al also showed lower global longitudinal and radial strain values compared to control in asymptomatic childhood cancer survivors with normal left ventricle ejection fraction and fractional shortening. 27 Majority of these findings of two-dimensional speckle tracking analysis-based strain studies are consistent with the present study's result such as reduced global longitudinal and circumferential strain and strain rate values in survivors of childhood cancer compared to controls and negative impact of total anthracycline dose on the left ventricle function. Based on the recommended imaging surveillance frequencies in the long-term follow-up guidelines published by the Children's Oncology Group, patients were classified as high risk who had ≥ 300 mg/m 2 cumulative anthracycline dose at any age.…”
supporting
confidence: 91%
“…Validation of LV longitudinal strain as a sensitive marker to detect early subclinical LV alterations in childhood cancer survivors remains to be demonstrated due to the lack of large-scale study. But in the recent years some small cohort studies have shown altered LV global longitudinal strain in adolescent and/or young adults with normal EF few months 37 , few years 38 , 39 and more than a decade 40 , 41 after chemotherapy. These studies corroborate our observations in our rodent model.…”
Section: Discussionmentioning
confidence: 99%
“…42 Thus, strain imaging may be a powerful tool to identify early myocardial injury in survivors of childhood cancer. 45 Recently, three-dimensional echocardiography, especially three-dimensional strain imaging, has shown potential superiority in diagnosing subclinical cardiotoxicity in adult-onset cancers. 46 As an alternative to echocardiography, cMRI has been used to monitor early and late cardiotoxicity in paediatric cancer patients and survivors.…”
Section: Imagingmentioning
confidence: 99%